The psychology of gender - Helgeson, Vicki S. (Routledge, 2018)
Noted for its fair and equal coverage of men and women, this book reviews the research and issues surrounding gender from multiple perspectives including psychology, sociology, anthropology, and public health, with an emphasis on the interaction between biological and social theories. The implications of social roles, status, and gender-related traits on relationships and health that are central to students' daily lives are emphasized throughout. Students learn how to distinguish the similarities and differences between the sexes and the theories that explain the differences. Methodological flaws that may impact the observance of sex differences are also examined.